Growth of Tropical Pines in Tamil Nadu in Relations to Soil Properties - Bari, P. A. Abdul; Prasad, K. G. (Indian Forester, 1987)
Pinus caribaea provenance FRI-649 was grown at Kolli Hills and Perumalmalal during 1979 and at Mahendragiri and Gudalur during 1981. Pinus oocarpa provenance FRI-650 was raised at Perumalmalai and Koill Hill during 1979, and provenances FRI-760 and 761 were raised at Koill Hill, Perumalmalai and Gudalur during 1979. The study has revealed that site and soli factors play a major role in the suitability of tropIcal pine species and their provenances. Solis of sandy loam texture seem to be ideal for raising these provenances, while solis of heavier texture seem to retard the growth after tbe 3rd year. The provenances grew well under low fertility conditions and a moderately acidic soli environment.